2021
DOI: 10.3390/w13141942
|View full text |Cite
|
Sign up to set email alerts
|

Avocado cv. Hass Needs Water Irrigation in Tropical Precipitation Regime: Evidence from Colombia

Abstract: The primary natural source of water for the Hass avocado crop in the tropics is precipitation. However, this is insufficient to provide most crops’ water requirements due to the spatial and temporal variability. This study aims to demonstrate that Hass avocado requires irrigation in Colombia, and this is done by analyzing the dynamics of local precipitation regimes and the influence of Intertropical Convergence Zone phenomena (ITCZ) on the irrigation requirement (IR). This study was carried out in Colombia’s c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Hass, encompassing both root, leaf, and fruit development, is intricately interlinked with the precipitation [ 43 ]. The availability of water in the soil assumes a central role in shaping the competition for resources between vegetative growth processes and fruit sets impacting avocado productivity [ 44 ]. This allocation of resources, in turn, affects the overall health and vitality of the avocado tree and directly influences the development of fruits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hass, encompassing both root, leaf, and fruit development, is intricately interlinked with the precipitation [ 43 ]. The availability of water in the soil assumes a central role in shaping the competition for resources between vegetative growth processes and fruit sets impacting avocado productivity [ 44 ]. This allocation of resources, in turn, affects the overall health and vitality of the avocado tree and directly influences the development of fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Hass across diverse production zones in Colombia. Initial investigations and climate-based simulations pertaining to the water equilibrium of this avocado cultivar have yielded insights [ 44 ]. Notably, it was deduced that a substantial portion of the producing regions experience a minimum of one month characterized by water insufficiency, thereby necessitating timely irrigation interventions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, avocado crops should be cultivated in areas where non or limited irrigation is required. Erazo-Mesa et al (2021) concluded that a large percentage of current and potential avocado growing areas in Colombia requires at least one month of irrigation during the year. According to the previous mentioned study, the area where the ORW is located requires irrigation from one to four months.…”
Section: Water and Foodmentioning
confidence: 99%
“…Unfortunately, such production has been conducted without technology, which has extended the agronomic knowledge gap (Ramírez- Gil et al, 2018a;Builes and Duque, 2020). Hass avocado in Colombia can be considered a rainfed crop because most farmers irrigate empirically once a week only when trees manifest water deficit signs or do not irrigate, but recently studies demonstrated that under tropical condition irrigation can be necessary in a few months a year (Erazo-Mesa et al, 2021). Therefore, Colombian Hass avocado farmers who adopt incipient or state of the art irrigation techniques can save water and mitigate the negative consequences of water scarcity and climate change on their agriculture production system in the future.…”
mentioning
confidence: 99%
“…Water scarcity and climate change will modify the water use in agriculture in the forthcoming years (FAO, 2020), including some avocado-producing areas, where changes in temperature and precipitation are projected with impacts on water balances (Ramírez-Gil et al, 2019). In addition, climatic variability under tropical conditions presents many adverse effects on crops as avocado (Ramírez-Gil et al, 2020;Erazo-Mesa et al, 2021). Climate variability is associated with seasonal and non-seasonal phenomena such as the Intertropical Convergence Zone (ITCZ) (Byrne et al, 2018;Mamalakis and Foufoula-Georgiou, 2018), and ENSO (El Niño Southern Oscillation) phenomena, respectively (McPhaden et al, 2006;McCabe and Wolock, 2013).…”
mentioning
confidence: 99%